Telecommunications and disaster management:: Participatory approaches and climate change adaptation - Poblet, Marta; Fünfgeld, Hartmut; McShane, Ian (Journal of Telecommunications and the Digital Economy, 2020)
This paper offers an overview of participatory approaches to disaster management and climate change adaptation as an introductory framework for the following five papers on the special theme of telecommunications and disaster management. While climate change is considered a societal challenge of global proportions, its impacts on human population and ecosystems take place at the local and regional levels. The geographic coordinates of disasters and emergencies, therefore, call for different location-based strategies that are embedded in their social and ecological context. Affordable, bottom-up, networked telecommunications meeting these conditions can be part of these strategies. The following papers in this issue offer a number of concepts, cases, and potential solutions.